Measuring the disparity of categorical risk among various sex offender risk assessment instruments - Jung, Sandy; Pham, Anna; Ennis, Liam (My University, 2013)
The focus on reducing sexual offending has led to the development of risk assessment measures and schemes to predict reoffending, prioritize the allocation of treatment and supervision resources, and ensure public safety. However, different risk assessment approaches may not always have high agreement on the same individual. In light of the research indicating that ordinal risk rankings are most commonly used and reported in various risk communications, this study compares four risk assessment approaches, namely, the Static-99R, Static-2002R, SORAG, and SVR-20, in order to evaluate the disparities among the risk categories of these measures. The results indicate that there are disparities between all of the risk measures, but many of these can be explained by structural differences and common overlapping dimensions in the measures. Possible explanations for and implications of the discrepancies, along with some guidance on determining which approach to use, are discussed.
Keywords: risk assessment; sex offending; Static-99R; disparity